2022
DOI: 10.1101/2022.01.20.477163
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutations of SARS-CoV-2 variants of concern escaping Spike-specific T cells

Abstract: The amino acid (AA) mutations that characterize the different variants of concern (VOCs), which replaced the ancestral SARS-CoV-2 Wuhan-Hu-1 isolate worldwide, provide biological advantages such as increased infectivity and partial escape from humoral immunity. Here we analyzed the impact of these mutations on vaccination- and infection-induced Spike-specific T cells. We confirmed that, in the majority of infected or vaccinated individuals, different mutations present in a single VOC (Delta) or a combined mosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
1
3
0
1
Order By: Relevance
“…Thus, these data do not support the notion of a selective pressure for mutation of the T cell epitopes at the population level. It is worth noting that while this has been confirmed at the experimental level exvivo, additional unknown factors may influence the expansion of specific T cell clones among the epitope pools considered herein and found to be more affected by viral mutations (Le Bert et al, 2022).…”
Section: Predicting the Impact Of Omicron Mutations In T Cell Epitopessupporting
confidence: 59%
“…Thus, these data do not support the notion of a selective pressure for mutation of the T cell epitopes at the population level. It is worth noting that while this has been confirmed at the experimental level exvivo, additional unknown factors may influence the expansion of specific T cell clones among the epitope pools considered herein and found to be more affected by viral mutations (Le Bert et al, 2022).…”
Section: Predicting the Impact Of Omicron Mutations In T Cell Epitopessupporting
confidence: 59%
“…Simultaneously, SARS-CoV-2 activates T cells in the first week of infection, and virus-specific memory CD4 + cells and CD8 + T cells reportedly peak within 2 weeks but remain detectable at lower levels for 100 or more days of observation. Grifoni et al 1 and others 5,6 have identified SARS-CoV-2-specific memory CD4 + T cells in up to 100% and CD8 + T cells in approximately 70% of patients recovering from COVID-19. Although severe COVID-19 is characterized by high-viral titers, dysregulated innate inflammatory cytokine and chemokine responses and prolonged lymphopenia, antibody-dependent enhancement or dominant CD4 + T H 2-type cytokines (eg, IL-4, IL-5, IL-13) do not appear to contribute to acute COVID-19 severity.The magnitude of the antibody and T-cell responses can differ and be discordant among individuals and is influenced by disease severity (asymptomatic, mild, moderate, or severe).…”
mentioning
confidence: 97%
“…SARS-CoV-2-specific CD4 + and CD8 + memory T cells are also generated in asymptomatic to severe disease, 1,5,6 which exhibit cytotoxic activities and express antiviral cytokines, features that may control viral replication and prevent recurrent severe infections. Analysis of CD4 + T cell responses indicate a predominant polarization to a T H 1 type, 1 although the roles T H 17 and T H 2 cytokines and cytotoxic T cells have in patients with COVID-19 acute respiratory distress syndrome needs greater clarity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Иммунный ответ против SARS CoV 2 иг рает решающую роль в определении клини ческого исхода как у взрослых, так и у детей [5]. Иммунитет к SARS CoV 2, вызванный ес тественной инфекцией, вероятно, опосредо ван комбинацией гуморального и клеточно го иммунитета [6]. В исследовании, сравни вающем детей и взрослых, выявили разные иммунные профили при коронавирусной инфекции, коррелирующие с менее тяжелы ми исходами у детей [7].…”
Section: Introductionunclassified